Laparoscopic cholecystectomy in an adult patient with a ventriculoperitoneal shunt system - González, Yazmin G.; Hernández, Reyger G. (International Journal of Research in Medical Sciences, 2024)
Adult patients with a ventriculoperitoneal shunt valve (VDVP) are not exempt from suffering from gastrointestinal diseases. Nowadays, with technological advances, it would be contradictory not to offer them the benefits of minimally invasive surgery. The case of a laparoscopic cholecystectomy of a 40-year-old male patient with VDVP who presented clinical signs of cholecystitis is presented. The patient's evolution was satisfactory and he was discharged home 72 hours after surgery. Currently, there are significant studies that demonstrate the benefit of minimally invasive surgery in patients with VDVP as a treatment for abdominal surgical pathologies, including biliary pathology. Therefore, in our experience and with the published cases, we conclude that patients with VDVP do benefit from minimally invasive surgery for any abdominal surgical pathology, including pathology of biliary origin.